(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The regulation on GMO products is a highly controversial field, because of different levels of competences and governance involved and due to the presence of conflicting interests. For this reason, the legal framework on food safety and scientific innovation in agriculture represents an interesting case study on multilevel governance. Moreover, GMO regulations are strictly connected to scientific progress and research, requiring an integration of different fields of expertise, such as law-maker, scientific experts and stakeholders. The paper takes into account the possible ways of legislative intervention, analyzing risks and benefits of the balancing between the need to guarantee food safety and the promotion of scientific development.